The Influence of Digital Technology on MSME Performance through Innovation, Financial Access, and Trust - Rinaldi Bursan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the impact of digital technology adoption on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, by considering the mediating roles of innovation capability, financial access, and business trust. MSMEs play a strategic role in the national economy, yet they continue to face various challenges in enhancing competitiveness and business performance. Digital technology adoption has emerged as a key strategy to drive operational transformation, expand market reach, and improve efficiency. This research adopts a quantitative approach using the Structural Equation Modeling (SEM) method to examine the relationships among variables. The findings indicate that digital technology adoption significantly affects MSME performance, both directly and through the enhancement of innovation capability and financial access. Furthermore, business trust also plays an important role as a psychological factor that reinforces commitment and business sustainability. These findings highlight the importance of policy support, digital infrastructure, financial literacy, and innovation capacity in strengthening the competitiveness of MSMEs in the digital economy era. This study provides both theoretical and practical contributions to the development of a digital-based MSME empowerment model in Indonesia.